International Differences in Well-Being 2010
DOI: 10.1093/acprof:oso/9780199732739.003.0001
|View full text |Cite
|
Sign up to set email alerts
|

1 Income’s Association with Judgments of Life Versus Feelings

Abstract: Evidence is presented that measures of subjective well-being vary along a dimension anchored at the two ends by evaluative judgments of life and experienced affect. A debate in recent decades has been focused on whether rising income increases the experience of well-being. We found that Judgment is more strongly associated with income, and with long-term changes of national income. Measures of feelings showed lower correlations with income in cross-sectional analyses, and lower associations with long-term risi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 10 publications
3
97
1
13
Order By: Relevance
“…Using the GHWBI, Kahneman & Deaton (2010) find that annual income's positive relationship with hedonic SWB is insignificant for income greater than $75,000 but find no such satiation point in the positive relationship with BPL. Diener et al (2010) find a similar pattern using the same questions from the Gallup World Poll.…”
Section: Dependent Variablesmentioning
confidence: 52%
“…Using the GHWBI, Kahneman & Deaton (2010) find that annual income's positive relationship with hedonic SWB is insignificant for income greater than $75,000 but find no such satiation point in the positive relationship with BPL. Diener et al (2010) find a similar pattern using the same questions from the Gallup World Poll.…”
Section: Dependent Variablesmentioning
confidence: 52%
“…They concluded that high income was related to life satisfaction but did not maintain for happiness, whereas low income was related both to low life evaluation and low emotional well-being. As suggested also by Diener, Kahneman, Tov and Arora (2010) and Oishi and Diener (2014) the different reports of life satisfaction and happiness reflect different conditions. The cognitive report of life evaluation reflects the prevalent economic conditions; whereas the affective report of happiness reflect the conditions of life, for instance the free time.…”
Section: Discussionmentioning
confidence: 67%
“…However, previous studies have mostly focused on affective well-being as a stable state for a period of time or certain pathological states rather than pleasant and unpleasant experiences in everyday life (Thoits 1989). They have relied on survey measures that ask respondents to provide an overall assessment of their emotional states, which can be influenced by their general levels of happiness and personal dispositions and also prone to retrospective and aggregation bias (Kahneman and Krueger 2006;Diener et al 2010). In order to measure daily affective experiences properly, Kahneman and Krueger (2006:9) argue that one needs to avoid "effects of judgment and of memory as much as possible."…”
Section: Religious Service Attendance and Affective Well-beingmentioning
confidence: 99%
“…The response to each of these questions is binary. I summarize these questions into a composite variable that measures daily affective balance by subtracting the mean of the four negative affect questions from the mean of the three positive ones and then standardizing it so that the mean of the variable is zero with standard deviation of one (Diener et al 2010). …”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation